2011
DOI: 10.1007/s00421-011-2282-8
|View full text |Cite
|
Sign up to set email alerts
|

Pedaling time variability is increased in dropped riding position

Abstract: Variability of cycle-to-cycle duration during a pedaling task is probably related to the rhythmic control of the lower limb muscles as in gait. Although walking variability has been extensively studied for its clinical and physiological implications, pedaling variability has received little attention. The present contribution determines the variability of the cycling time during a 10-min exercise as a function of upper body position. Nine healthy males were required to pedal on cycle-ergometer at a self-select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 14 publications
2
32
0
Order By: Relevance
“…Moreover, preliminary data from a pilot study done with the SRM (Schoberer Rad Messtechnik, Welldorf, Germany) power monitoring system suggested that the maximal power output in Watts (calculated from the torque and angular speed of the crank) was at the crank angle of 71°, independently from the angular speed used (data not shown). Therefore, we also tested the effect of two different initial crank angles: 47°a nd 71°; this setting [38] was calibrated for each start with goniometer (Nokia C6, Finland; error 0.1°). Subjects repeated the test in the same condition four times.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, preliminary data from a pilot study done with the SRM (Schoberer Rad Messtechnik, Welldorf, Germany) power monitoring system suggested that the maximal power output in Watts (calculated from the torque and angular speed of the crank) was at the crank angle of 71°, independently from the angular speed used (data not shown). Therefore, we also tested the effect of two different initial crank angles: 47°a nd 71°; this setting [38] was calibrated for each start with goniometer (Nokia C6, Finland; error 0.1°). Subjects repeated the test in the same condition four times.…”
Section: Methodsmentioning
confidence: 99%
“…Th ese works start from the improvement of heart and lung effi cacy to the enhancement of joint function (Padulo, Di Capua & Viggiano, 2012;Padulo et al, 2013;Oliva, Osti, Padulo & Maff ulli, 2014;Gheller et al, 2015); from regulating blood sugar and fat to that of the sleep-wake cycle (Matinez-Gomez et al, 2010;Umpierre et al, 2011;Lang et al, 2013). Obviously, among all the organs of our body, the brain is richly benefi tted by movement, both structurally and functionally.…”
Section: Introductionmentioning
confidence: 99%
“…The participant's hand position was similar to the stationary cycling task (bottom of the handle bar) and the gear selected was consistent with the stationary cycling task 19 . The same bicycle was used to test all participants.…”
Section: Track Measures and Proceduresmentioning
confidence: 99%
“…However, to verify the effect of the two riding postures on instantaneous cycling speed in a real cycling environment, participants were also required to perform a similar experimental protocol on a race bicycle on a sport-specific oval track. This protocol has been used previously to assess cycling performance 19 .…”
mentioning
confidence: 99%
See 1 more Smart Citation